Laparoscopic Versus Open Surgery for Early-Stage Intrahepatic Cholangiocarcinoma After Mastering the Learning Curve: A Multicenter Data-Based Matched Study - Jinhuan, Yang; Yi, Wang; Yuanwen, Zheng; Delin, Ma; Xiaotian, Chen; Yan, Wang; Liming, Deng; Haitao, Yu; Lijun, Wu; Tuo, Deng; Kaiyu, Chen; Jiawei, Hu; et al. (Frontiers in Oncology, 2022)
Background Surgical resection is the only widely accepted curative method for intrahepatic cholangiocarcinoma (ICC). However, little is known about the efficacy of laparoscopic liver resection for ICC, especially in patients with early-stage disease. The aim of this study was to compare the short-term and long-term effects of laparoscopy and open surgery for the treatment of ICC. Methods Data from 1084 patients treated at 3 hospitals from January 2011 to December 2018 were selected and analyzed. Propensity score matching was performed to compare the long-term outcomes (overall survival and recurrence-free survival) and short-term outcomes (perioperative outcomes) of all-stage and early-stage patients. Results After matching, 244 patients (122 vs. 122) in the all-stage group and 65 patients (27 vs. 38) in the early-stage group were included. The baseline of the two groups was balanced and no significant differences were found in sex or age. The short-term results of the laparoscopic group were better than those of the open group, including less blood loss (blood loss≥400 ml 27 (22.1%) vs. 6 (4.92%), p＜0.001 for all-stage, 12 (31.6%) vs. 2 (7.41%), p=0.042 for early stage), shorter surgery (200 [141; 249] min vs. 125 [115; 222] min, p=0.025 for early stage) and shorter hospital stay (11.0 [9.00; 16.0] days vs. 9.00 [7.00; 12.0] days, p＜0.001 for all stage, 11.0 [8.50; 17.8] days vs. 9.00 [6.50; 11.0] days, p=0.011 for early stage). Regarding long-term outcomes, no significant differences were found for all-stage patients, while there were significant differences observed for the early-stage group (p=0.013 for OS, p=0.014 for RFS). For the early-stage patients, the 1-, 3-, and 5-year OS rates of the OLR group were 84.2%, 65.8%, 41.1%, respectively, and those of the LLR group were 100%, 90.9%, 90.9%, respectively. The RFS rates of the OLR group were 84.2%, 66.7%, 41.7%, respectively, and those of the LLR group were and 92.3%, 92.3%, 92.3%, respectively. Conclusion Patients treated with laparoscopy seemed to have better short-term outcomes, such as less blood loss, shorter operation duration and shorter hospital stay, than patients undergoing open surgery. Based on the long-term results, laparoscopic treatment for early ICC may have certain advantages.